PP.30.33: IS IT TIME FOR CHRONOTHERAPY? COMPLIANCE WITH ANTIHYPERTENSIVE THERAPY. (June 2015) - De Rosa, M.; Leosco, D.; Abete, P.; Ferrara, N.
Abstract : Objective: The chronotherapy (C)—timing, a treatment based on a patient(P)'s biological clock, could improve the treatment (T) of hypertension (H). Reported rates of patients (P) adherence (A) may be confounded by several variables, potentially including multiple dosing and time-of-day of ingestion. Design and method: We evaluated the role of ingestion-time of the medications (M) on the A to H treatment among 101 treated hypertensives, 64.5 ± 12.2aged, and the prospectively cardiovascular risk by 48 h ambulatory blood pressure (BP) monitoring (ABPM). Among them, 42 were ingesting all BP-lowering M upon awakening (group 1), 28 at bedtime (group 2), and 31 upon awakening and at bedtime (group 3), respectively. P were instructed to always keep their M at the bedside table. A was evaluated using the Brief Medication Questionnaire. Results: Full A (score 0 in the test) was equivalent among all T-time regimens (86.1%, 85.9%, and 86.2% in groups 1, 2, and 3, respectively; P = 0.799). Prevalence of poor (p) and very p A (scores 1 and > 1, respectively) was also independent of H T-time (p A: 10.9, 11.0, and 10.3%; very p A: 2.9, 2.4, and 3.3% in groups 1, 2, and 3, respectively; P = 0.422). There were no differences in full A among P as a function of the prescribed number of M, it being 85.6, 8.9, 85.5, 85.4, and 84.4% in P ingesting 1, 2, 3, 4, or > 4 M, respectively (P = 0.339). Conclusions: Our findings indicate equivalent A to H pharmacotherapy in P ingesting M either at bedtime or upon awakening. A simple message enforced by health-care personnel, using proper circadian timing in relation to the rest-activity cycle instead of meaningless clock-time for prescription of T, and P evaluation by ABPM, all might be factors associated with increased compliance, independent of T-time and number of M required to achieve proper BP control. Nocturnal BP regulation is significantly better achieved at bedtime as compared with morning administration of drugs without any loss in efficacy during diurnal active hours, changing in the dose-response curve.